Economic openness, innovation and economic growth: Nonlinear relationships based on policy support - Ya Wen; Pingting Song; Chen Gao; Deyong Yang (Heliyon, 2023)
Whether economic openness (EO) is conducive to promoting economic growth has become a common concern of many scholars and policymakers in China. Based on the panel sample data of 30 provinces in China from 2004 to 2018, this paper adopts an empirical model to test the relationship between EO and regional economic growth. The study identifies that expanding EO increases regional economic growth. After dealing with endogeneity issues, the results remain robust. The results of the mediation effect model show that technological innovation is an important channel for EO to accelerate economic growth. With the improvement of regional economic development, the benefits of EO will increase. However, its positive effect has slowed down in regions with very high levels of economic development. The outbreak of the financial crisis has weakened the driving force of EO on economic growth, while the Belt and Road Initiative has strengthened the positive impact of EO. In addition, when introducing the threshold variable of policy support to examine the nonlinear relationship between variables, it is found that deepening the policy intensity will significantly improve economic growth due to the benefits of EO.